Bioeconomic analysis of the commercial production of Nile tilapia with biofloc and green water technologies - Berenice Suárez-Puerto; Marcelo Araneda; Mariel Gullian-Klanian (Aquaculture and Fisheries)
This study presents a bioeconomic model after analyzing the commercial profitability of Nile tilapia under biofloc (BFT) and green water (GWT) technologies. Environmental stochasticity was evaluated using the parameters obtained in Yucatan's rainy (RN) and dry (DR) seasons. The productive impact was measured by analyzing the 10-year cash flow. Both systems demonstrated profitability with a positive NPV and 450 g harvest weight in the short term. The unit cost of production results for the GWT was lower than for the BFT. The long-term simulation involved an investment of $410,279 USD for 30 tanks, resulting in a positive return for GWT. BFT showed negative long-term profitability at the current selling price ($2.36 USD/kg). Profitability improved as the sales price increased by 11% and 22% for RN-BFT and DR-BFT, respectively. This bioeconomic model is pioneering in tilapia production in BFT and GWT and provides valuable data to achieve better yield and profitability.